Discovering the Technology Adoption of Local OTOP Entrepreneurs in Pattani: Exploratory of the Network Structure - Mudor, Hamdia; Matcha, Wannisa (International Journal of Integrated Engineering, 2022)
This paper explores the technology adoption of the local entrepreneurs and the intention to use the technology i.e., objectives and technology adoption behaviors. 150 local entrepreneurs located in Pattani province in Thailand voluntarily provided information. They were asked to fill in a set of questionnaires regarding the objectives, type, frequency, and time of adopted the technology. The data analytics techniques, including, hierarchical clustering, Epistemic Network Analysis (ENA) were used to explore the qualitative data. Clustering enabled to categorize the entrepreneurs into groups based on the similarity of technology adoption objectives. ENA illustrated the connections of the studied elements and formed a structure of a network. The results suggested that currently, local entrepreneurs adopt the commonly use social media technology in order to reach out to the targeted customers. The duration of technology adoption was different between the two groups. This exploration suggested that the intention of using the technology and the technology adoption behaviors were different among the local entrepreneurs who sell the different types of products. The main implication derived from this study are two twofold. That is, there are differences in terms of technology adoption between local entrepreneurs who sales necessary goods and unnecessary goods. Government and related sectors may use this insight in order to design the campaign or provide the necessary training on how to use technology effectively.